IMPLEMENTASI PEMBELAJARAN TEKS NEGOSIASI DALAM KURIKULUM MERDEKA - Rosmawaty; Zahwa Az-zahra Alasta Selian; Rahma Putri Inaya Harahap; Suci Fitria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of negotiation text learning in the Independent Curriculum and identify strategies, challenges, and solutions. The method used was a qualitative approach with library research, utilizing various sources such as books, scientific journals, and educational policy documents. The results indicate that negotiation text learning in the Independent Curriculum emphasizes the development of communication skills, critical thinking, and the ability to interact contextually. Learning implementation is carried out through planning based on Learning Outcomes (CP) and Learning Objectives (ATP), implementation using active learning models such as role-play, problem-based learning, and project-based learning, and authentic evaluation covering aspects of process, product, and attitude. However, several challenges remain, such as limited teacher understanding, a lack of learning media, and variations in student abilities. Therefore, strengthening strategies are needed, including teacher training, the use of technology, and local context-based learning. Therefore, negotiation text learning in the Independent Curriculum has the potential to improve students' communication competencies in a more applicable and relevant way to real life.